Minhaj Dakwah Masakini: Suatu Pengenalan - Mohd. Zin, Ab. Aziz (Jurnal Usuluddin, 1996)
One of the problems which arises among du’at is the problem of vagueness in following the best minhaj in da’wah. Therefore, this article exposes the need for a minhaj in da’wah and the criterion to justify the best minhaj according to the target audience. This article also systematically uncovers the situations where a certain minhaj is appropriate such as the content and the medium of da’wah. It also reveals the methods to influence the target of da’wah.